La prueba electrónica en el ámbito de la propiedad intelectual (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The widespread use of digital systems is proving to be, among other issues, a serious threat to intellectual property rights. We are witnessing an ever-increasing lack of protection of the right-holder in controlling the publication and/or distribution ofcopies of his work. This undeniable fact has two sides to it, on the one hand the absence of legislation which makes it impossible for a clear regulatory framework tobe put into place that determines the illegality of the appropriation without consent of electronic copies. On the other hand and even in the hypothetical event that aregulatory framework did exist, the difficulty in proving that the right-holders’ rightshave been infringed.The reason for the difficulty in proving infringement lies in the fact that evidencingthe infringement of ownership rights in an electronic arena, is subject to the appearance of a new source of proof, the computer file, which has certain characteristics that need to be borne in mind.
Keywords: Intellectual property; electronic proof; electronic copy; downloading; P2P; conflict with fundamental rights; value as evidence; computer file; source of proof; means of proof.